Digital-Based Learning for Writing Using MakeBeliefsomix Cartoon Application - Ryandini, Elda Yulia; Utomo, Dias Tiara Putri; Indasari, Nur Laili (Journal of Digital Learning and Education, 2024)
In teaching and learning process, the use of digital tools urges the educators to integrate them as the use of innovative technology. The implementation of digital tools in learning definitely can bring various experiences for students when they mix up with the new tools in learning. Students can be more interested in involving in the learning activity since they are familiar with the media used in daily activity. Teachers can make use of digital-based learning for writing activity such as using MakeBeliefsComix cartoon application to motivate students to write in English. Foreign learners always encounter difficulties in writing as they need to comprehend some aspects such as mechanic, grammar, and sentence error. This study aims to analyze students’ writing result using digital comic of MakeBeliefsComix and their perceptions using digital comic for writing activity. Researchers employed qualitative approach with 15 documents from Management students’ writing results and 10 students as the interviewees. The results show that students mostly encounter writing difficulties in mechanics of punctuation and capitalization; and grammar in the case of translation sentence; question sentence; the use of verb 1, verb 2, and verb 3; modal verb, and the application of article ‘a’ although they do not really affect the writing ideas. From those difficulties in writing, students still get motivated to write using MakeBeliefsComix application identified from their perception that the use of digital comic or digital-based learning for writing were interesting, not boring, giving them new experience, and fun. It motivated them to write and could develop their writing.